Theoretical prediction of tunability enhancement in coplanar-type capacitors by adopting embedded electrodes structure - Kim, DY; Yoon, Seok Jin (KOREAN PHYSICAL SOC, 2005)
Embedded electrodes structure is introduced in microwave tunable capacitors. In theoretical estimation with reasonable device parameters, embedded-electrodes-structured tunable capacitors show higher tunability than coplanar-type ones. The embedded electrodes structure is also predicted to improve communication quality factor of the tunable capacitors.
Keywords: DIELECTRIC-PROPERTIES; THIN-FILMS